Black rice extract extends the lifespan of fruit flies. - Zuo, Y.; Peng, C.; Liang, Y.; Ma, K.Y.; Yu, H.; Edwin Chan, H.Y.; Chen, Z.Y. (Food & function, 2012)
Black rice is rich in anthocyanin antioxidants. The present study investigated the lifespan-prolonging activity of black rice extracts (BREs) and its effect on gene expressions of CuZnSOD (SOD1), MnSOD (SOD2), catalase (CAT), methuselah (Mth) and Rpn11 involved in the antioxidant system and ageing of fruit flies. The OR wild type fly was maintained on a control diet or two experimental diets containing 10 mg ml(-1) BRE (BRE10) or 30 mg ml(-1) BRE (BRE30). Results demonstrated that BRE30 could prolong the mean lifespan of fruit flies by 14%, accompanied with up-regulation of mRNA SOD1, SOD2, CAT and Rpn11, and with down-regulation of Mth. It was also found that BRE30 could attenuate the paraquat-induced neurodegeneration in OR wild type flies accompanied by up-regulation of SOD1, SOD2, CAT and Rpn11. In addition, BRE30 supplementation increased the survival time of OR wild type flies and Alzheimer transgenic flies A?42 33769 with chronic exposure to paraquat. It was concluded that BREs could extend the lifespan of fruit flies, most likely by regulating the genes of SOD1, SOD2, CAT, Mth and Rpn11 at the transcriptional level.